POLA ASUH ORANG TUA MUDA TERHADAP PERKEMBANGAN ANAK USIA DINI DI DESA TOGID KECAMATAN TUTUYAN KABUPATEN BOLAANG MONGONDOW TIMUR - Makalalag, Winarni (Institut Agama Islam Negeri Bone, 2024)
The village of Togid in the Tutuyan district of East Bolaang Mongondow regency is one of the areas where underage couples have married and become parents. These young parents often pay little attention to the parenting patterns they apply to early childhood development and tend to use uncreative parenting approaches. This study employed a qualitative research method. Data were collected through observation, interviews, and documentation. The findings show three parenting styles adopted by young parents, each characterized by an inconsistent approach. In the democratic parenting style, children are generally allowed to express their thoughts, opinions, and feelings. In the permissive parenting style, parents prioritize avoiding conflict, often giving in to the child's wishes and providing minimal supervision. In the authoritarian style, young parents respond to mistakes or undesired behavior by yelling or using physical force. The impact of young parents' parenting styles on early childhood development can be seen in two less favorable developmental aspects. First, moral development, where children display poor moral behavior, such as defying their parents or using inappropriate language. Second, social-emotional development, where children exhibit negative emotions and may even resort to physical aggression.